Oxynitrides decorated 316L SS for potential bioimplant application. (7th March 2018) - Kaliaraj, Gobi Saravanan; Kumar, N
Abstract: Titanium oxynitride (TiON) and zirconium oxynitride (ZrON) were deposited onto 316L stainless steel (316L SS) using reactive magnetron sputtering technique. The monoclinic and cubic phase of TiON and ZrON were obtained by x-ray diffraction (XRD). Nanoindentation and wear test analysis exhibited the better mechanical properties of TiON and ZrON films. Wettability studies showed hydrophilic nature on coated films; whereas bare 316L SS substrate was least hydrophilic. Drastic reduction of bacterial adhesion ( Pseudomonas aeruginosa ), as well as biofilm formation, was observed in both the films at different time duration. TiON and ZrON films were exhibited excellent hemocompatibility by preventing the platelet activation. Furthermore, the coated films exhibited corrosion protection in presence and absence of hydrogen peroxide (H2 O2 ) in artificial blood plasma (ABP) solution.